The Politics of Legal Reform - Paul H. Brietzke (Washington University Global Studies Law Review, 2004)
This Article goes back to the future, by beginning where opportunities for the advance or (more frequently) the retreat of law reforms begin: with the political processes that are usually ignored by analysts. The thesis of law reforms in transition countries, which is called the “good governance thesis” or even the “rule of law”, is a litany recited in the International Monetary Fund (IMF) and the World Bank (WB) with a religious fervor: transparency, public participation, accountability, and predictability. Unfortunately, attempts to implement these qualities call forth their antithesis: corruption, organized violence, such as torture or terrorism that the state directs or cannot control, and other abuses of interchangeable wealth and power by incumbent elites. Thesis and antithesis play out in a dialectic or conflict operating among values, incentives, actions, and organizations. Reforms, democratization, and development thus advance or mostly, because the conflict is an uneven one, retreat, dialectically and along many fronts at once.
Keywords: Legal reform; International